2006
DOI: 10.1149/1.2177047
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature (<100°C) Deposition of Aluminum Oxide Thin Films by ALD with O[sub 3] as Oxidant

Abstract: Al 2 O 3 films were deposited by atomic layer deposition ͑ALD͒ using trimethylaluminum and O 3 as precursor and oxidant, respectively, at growth temperatures ranging from room temperature to 300°C on Si͑100͒ substrates. Growth rate and refractive index of the Al 2 O 3 films decreased from 0.20 to 0.08 nm/cycle and increased from 1.52 to 1.65, respectively, with increasing growth temperature. The dielectric constant slightly increased from 6.8 to 8 with increasing growth temperature in the same temperature rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
116
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 28 publications
19
116
0
Order By: Relevance
“…Alumina grown this way yielded a more dense coating with the FDTD model fit parameters of n c = 1.4 and t = 4 nm. Unlike sample A, sample B was not exposed to air in between the successive layers, therefore the alumina growth rate is slightly higher, 1.25Å/cycle on the top surface, or 2.5Å/cycle inside the NG, which is consistent with growth rates reported for alumina ALD at room temperate under similar conditions [74][75][76].…”
Section: Resonance Tuningsupporting
confidence: 84%
“…Alumina grown this way yielded a more dense coating with the FDTD model fit parameters of n c = 1.4 and t = 4 nm. Unlike sample A, sample B was not exposed to air in between the successive layers, therefore the alumina growth rate is slightly higher, 1.25Å/cycle on the top surface, or 2.5Å/cycle inside the NG, which is consistent with growth rates reported for alumina ALD at room temperate under similar conditions [74][75][76].…”
Section: Resonance Tuningsupporting
confidence: 84%
“…For instance, ozone (O 3 ) can be used as an oxidant. 9 However, this is slightly more complex as it requires an ozone generator with a sufficiently high O 3 production rate. Particularly when going to high throughput applications where large amounts of ozone are required, this might become too costly.…”
Section: B Alternatives For Watermentioning
confidence: 99%
“…Carbon atoms are common impurities affecting the passivation quality of Al2O3 layers [5,7,8], and are considered harmful for surface passivation. Although ozone possesses a stronger oxidation potential than water, and has potentially beneficial effect on the reduction of impurity concentrations, as shown in previous studies [5,[8][9][10], other studies have also reported relatively high carbon concentration in ozone-based ALD films [11,12]. Despite this possible drawback, ozone-based ALD Al2O3 shows promising surface passivation quality [6,13].…”
Section: Introductionmentioning
confidence: 96%